Cardiovascular medication reconciliation in hypertensive diabetic outpatients at Chris Hani Baragwanath academic hospital - Laher, Zaheer (My University, 2016)
Background Medication reconciliation is the process of creating accurate lists of a patient’s medication and comparing them to the treating physician’s script, finding factors that influence adherence. Objectives To determine any discordance between actual medication diabetic hypertensive patients at the specialist endocrine outpatient department at CHBH are taking and those on the physician’s script, and to determine factors linked to poor adherence. Results The mean age of the patients was 60 years, and female majority of 73%. Fifty nine percent of patients had a maximum of primary school education and 17% had no schooling. Majority of drugs were taken incorrectly, attributed to stock issues, patient error and use of generic medication. Gender, age and whether the doctor routinely tells the patient of any adjustments showed no association. Conclusion Poor adherence was attributed to the patient’s poor knowledge of the medications. Adherence to the dosage of drugs was shown to be dependent on a patient’s level of education.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg. This work is done in fulfilment of the requirements for the degree Master of Medicine in Internal Medicine Johannesburg 2015